Analisis Ukuran Perusahaan, Profitabilitas, dan Pertumbuhan Terhadap Nilai Perusahaan yang Dimediasi Oleh Pengungkapan Emisi Karbon (Studi Pada Sub Sektor Food & Beverage yang Terdaftar di BEI Periode 2018-2022) - Maratusholihah Abd Latif; Mukhzarudfa Mukhzarudfa; Rita Friyani (JAKU (Jurnal Akuntansi & Keuangan Unja) (E-Journal), 2023)
This study aimed to analyze the effect of company size, profitability, and growth on company value through disclosure of carbon emissions. The population of this study were food and beverage industry companies on the Indonesia Stock Exchange for the period 2018 - 2022. The sample were selected from the population with the criteria that the companies were listed company on the IDX successively and report disclosure of carbon emissions in the annual report. The number of samples in this study was 17 companies with observations for 5 years. Data analysis used path analysis and Sobel tests are used to observe indirect influences. The results of this study indicated that company size and profitability had a direct effect on disclosure of carbon emissions and firm value, while growth had no direct effect on disclosure of carbon emissions and firm value. The results of this study also showed that company size, profitability and growth did not have an indirect effect on firm value mediated by disclosure of carbon emissions.